2013
DOI: 10.4028/www.scientific.net/aef.10.351
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Carrying Multiple Pillion Riders on the Route to School

Abstract: Abstract.A cross-sectional observation survey was carried out among 6 to 12 year old child pillion riders travelling to and from schools by motorcycle. The study focuses on the prevalence of carrying multiple child pillion riders at the same time, to determine the relationship between child pillion riders' safety helmet compliance, and their seating position and foot peg use. A total of 701 riders and 913 school children were observed. Riders' safety helmet use rate was found to be significantly higher (66.8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Norlen et al of MIROS, had conducted multiple studies on seatbelt wearing and several studies have been selected to show the impact of rear seatbelt law introduced in [22,43,44]. It is clear that rear seatbelt wearing is still low after about six years since the enforceable date, as supported by the latest findings by Aqbal et al (2014) and Wahida et al (2015) [11,27]. A spike only occurred in the earlier months of rear seatbelt law introduction, in which the result was derived from a nationwide level study.…”
Section: Legislative Frameworksupporting
confidence: 49%
See 2 more Smart Citations
“…Norlen et al of MIROS, had conducted multiple studies on seatbelt wearing and several studies have been selected to show the impact of rear seatbelt law introduced in [22,43,44]. It is clear that rear seatbelt wearing is still low after about six years since the enforceable date, as supported by the latest findings by Aqbal et al (2014) and Wahida et al (2015) [11,27]. A spike only occurred in the earlier months of rear seatbelt law introduction, in which the result was derived from a nationwide level study.…”
Section: Legislative Frameworksupporting
confidence: 49%
“…Compared to seatbelt wearing, most motorcyclists do not place importance on helmet as their only protection, especially in the suburban and rural areas [10,14,46]. The compliance rate was observed as low as 42%, with another 51% not properly wearing their helmet, even during festive seasons when enforcement activities are intensely carried out in the country [27]. Helmet for the child occupant poses a more serious concern, as the study by Noor Faradila et al (2013) and Rabihah et al (2013) confirmed that the wearing rate is still low [27,46].…”
Section: Related Research Findings -Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in both on-road and off-road samples, males are more commonly injured as riders, and females as passengers 5 9 20. For exhaust system burns, males and females are affected relatively evenly;21 however, females primarily sustain burns as passengers, while males are more often injured as riders 22…”
Section: Resultsmentioning
confidence: 99%
“…However, there does not appear to be clear evidence for these limits8 nor much study of the physical limits to safe travel as a pillion passenger 20. A Malaysian study examined the match between child anthropometry and pillion seat design and found children approximating 7 year olds could not reach the foot pegs.…”
Section: Resultsmentioning
confidence: 99%